PEMBUATAN BIOBRIKET ARANG BERBASIS TANDAN KOSONG KELAPA SAWIT DAN AMPAS TEBU SEBAGAI SUMBER ENERGI ALTERNATIF YANG RAMAH LINGKUNGAN - Giyanto; Muhammad Wahid Hamdi (Institut Teknologi Sawit Indonesia (ITSI), 2020)
Briquettes are solid fuels that can be used as alternative energy. This research aims to determine the optimalratio of raw materials with adhesive content at about 10% constantly. The stages of this research were asfollows: 1) Sampling of raw materials, 2) Drying and decomposition of raw materials, 3) CarbonizationProcess, 4) Milling. 5) Composition Treatment, 6) Pressing and quality analysis of briquettes. The data of thisresearch were obtained by measuring calorific value, moisture content, ash content, density, compressivestrength, and combustion rate. The ratio between empty bunch : bagasse respectively was depended on100%: 0%, 75%: 25%, 50%: 50%, 25%: 75%, 0%: 100%. The Parameters of treatments were calorific value,moisture content, ash content, density, compressive strength, and combusition rate to find out the bestparameters. The result of this research shows the that the combination of empty bunch and baggase gave theeffect to the qualities. The highest calorific value was showed in the ratio empty bunch : baggase (100% : 0%)with average HHV value; the lowest average of moisture content ; the lowest ash content; density;compressive strength value; and combustion rate respectively 5889 cal/gr; 2,81%; 20%; 0,941 gr/ml;1,82N/cm2;0,00223gr/second.